Soliton solutions of the improved perturbed nonlinear Schrödinger equation having parabolic law with non-local nonlinearity in the presence of chromatic and spatio-temporal dispersion terms - Esen, Handenur; Onder, Ismail; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa (IOP Publishing Ltd, 2024)
This paper was organized to examine the analytical solutions of the improved perturbed parabolic-law nonlinear Schrodinger equation including non-local nonlinearity in the presence of chromatic and spatio-temporal dispersion. This model mostly makes use of studying the propagation of optical pulses in fiber optic communication systems. We performed the Sinh-Gordon equation expansion method so that we produce the analytical solutions of the model under consideration. It was confirmed that the acquired solutions satisfy the main model. Therefore, bright and dark soliton solutions were retrieved; besides, various 3D and 2D graphical illustrations of the solitons were demonstrated via appropriate values of the parameters. Furthermore, this manuscript focused on the parameters' effect on the acquired solitons behavior.
Keywords: parabolic law nonlinearity; non-local nonlinearity; group velocity dispersion; spatio-temporal dispersion; Sinh-Gordon equation expansion method; soliton solutions; OPTICAL SOLITONS; Physics